Determinants of Digital Payment Adoption Among The Millennial Generation in Semarang City - Tavika Trirahma; Edwin Zusrony; Myra Andriana (ITB AAS Indonesia Surakarta, 2025)
This study investigates the impact of perceived ease, perceived security, and social influence on the acceptance of digital payments among millennials. This research use quantitative methodologies. The study employs primary data collected through online surveys with a Likert scale ranging from 1 to 5 points. The study population comprises all millennials residing in Semarang. The sample strategy employs non-random sampling via a purposeful sampling method. The overall number of participants is 80 millennials aged 28 to 40 years. The data analysis method employs multiple linear regression, and the data is processed with the SmartPLS 4.1.1.2 program. This study illustrates that both perceived simplicity and perceived security considerably and favorably affect the uptake of digital payments. Social influence is a factor that does not substantially impact the adoption of digital payments. This research provides benefits for the millennial generation in decision-making concerning the use of digital payment applications, shaped by many exogenous variables affecting endogenous variables.